2011
DOI: 10.1021/mz2000237
|View full text |Cite
|
Sign up to set email alerts
|

Precise Acid Copolymer Exhibits a Face-Centered Cubic Structure

Abstract: A linear polyethylene precisely functionalized with geminal phosphonic acid pendants on every 21st carbon atom exhibits face-centered cubic (FCC) packing of acid aggregates. X-ray scattering from isotropic films result in higher-order scattering peaks used to determine the lattice parameter at room temperature (a FCC = 4.19 nm) and above the melting temperature of the polyethylene matrix (a FCC = 4.06 nm). Upon stretching the precise acid copolymer, an anisotropic scattering pattern featuring two coexisting cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 8 publications
3
47
0
Order By: Relevance
“…One zinc-neutralized system additionally displays long range cubic ordering of ionic aggregates [10]. A cubic ordering of aggregates has also recently been observed in a precise polyethylene copolymer with pendant phosphonic acid groups [4].…”
Section: Atomistic MD Simulationsmentioning
confidence: 80%
“…One zinc-neutralized system additionally displays long range cubic ordering of ionic aggregates [10]. A cubic ordering of aggregates has also recently been observed in a precise polyethylene copolymer with pendant phosphonic acid groups [4].…”
Section: Atomistic MD Simulationsmentioning
confidence: 80%
“…An isotropic PA polymer film displayed uniform scattering rings at the 2D X‐ray scattering detector (Figure via X‐ray scattering profile at room temperature). Winey and co‐workers confirmed that the behavior was not consistent with the previously accepted modified liquid‐like scattering model of monodisperse spheres …”
Section: Functionalized Admet–pementioning
confidence: 86%
“…Recent advances in catalyst chemistry have enabled synthesis of linear polyethylenes via ADMET with precisely placed functional groups . For example, polyethylenes with acidic side groups form various polymer architectures (Figure ) such as acid dimers, ionic and/or neutral aggregates, and polymer nanocrystals . Commercial preparations of acid copolymers typically exhibit unpredictable degrees of microstructural irregularities leading to a diverse assortment of bulk properties and potential applications .…”
Section: Functionalized Admet–pementioning
confidence: 99%
See 2 more Smart Citations